Avaliação da resposta eletrocardiográfica e sorológica ao tratamento com benzonidazol em pacientes na fase crônica da doença de Chagas - Andrade, Mônica Coelho (2013)
Chagas disease (CD) is a pathology of endemic nature, caused by the protozoan Trypanosoma cruzi, with pronounced relevance between heart disease. It was officially described in 1909 and even after more than a century of its discovery is still a public health problem. The aim of this study was to evaluate the effectiveness of chemotherapy with Benznidazole (Bz) in patients with chronic Chagas disease by serological analysis and electrocardiography. This is a prospective non-concurrent and concurrent study, where patients were followed serologically once a year after treatment, from 2005, 2006 or 2007 (before treatment) until 2011. The electrocardiographic evaluation was performed at baseline (2005-2007) and end of the study (2011). The patients were treated with Bz in dose of 5mg/kg/day in two to three daily doses for 60 days. The serological analysis was conducted, through the techniques of ELISA (enzyme immunoassay) and IIF (indirect immunofluorescence). The electrocardiographic evaluation was performed at the University Hospital Walter Cantídio through the electrocardiograms (ECG) available in patient charts. This study followed 31 patients, 20 (64,5%) male and 11 (35,5%) female, from 25 to 64 years, where 51.6% (16/31) did not finish high school and 22,6% (7/31) were farmers. Serological analysis by ELISA demonstrated a significant decrease in the optical density of the samples collected before (2005 to 2007) when compared with the samples after treatment (2011). Now with regard to IIF, patients remained unchanged during the segment (variation in a maximum of a dilution of the sample between baseline and 2011). Regarding the electrocardiographic evaluation, 76.2% (16/21) showed maintenance of electrocardiographic reports throughout the study, with the exception of cinco cases. One patient was excluded from analysis electrocardiographic (there wasn’t ECG performed in 2011) required a defibrillator implantation during follow-up (2010). In conclusion, one can say that although Bz presents limited effectiveness in patients in the chronic phase of CD, this study demonstrated a beneficial effect of the drug in most followed patients, as the majority of these reports showed maintenance of electrocardiographic and serology showed a downward trend. However, it is necessary a longer segment, since the follow-up period of this study (5-7 years) is considered short for patients in the chronic phase of the disease.